USAGE OF SHEAR THICKENING FLUID TO ENHANCE THE IMPACT PROPERTY OF KEVLAR FIBERS WITHIN A COMPOSITE MATERIAL (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2024)
In the current work, multi-layers were manufactured based on epoxy polymer using Nano Graphine and aramid (Kevlar) fiber as fillers. Nano Graphine was added by 1, 2, 3 wt% to the epoxy matrix and the Kevlar sheets were embedded within these composites. The die casting process is used to prepare the composite plate with thickness of 3mm. To improve the performance of Kevlar fibers, these fibers impregnated in the shear thickening fluid (STF), which is composed of fumed Nano silica and polyethylene glycol (PEG). By using ultrasonic dispersion method to dispersion nano particles into the composite and then preparation the sample ,some mechanical (tensile strength, impact strength, and hardness test) According to our findings, the best result was for (2%wt Gnps) the tensile, impact strength, and hardness values 260.2 MPa, 51.194 kJ/m2, and 69.5 MPa, respectively, by soaking these fabrics with shear thickening fluids we observe improve the mechanical properties for the composite materials for the 2%wt Gnps percentage (tensile strength, impact strength, and hardness ) are (290.9 MPa, 77.82 kJ/m2, and 72.22 MPa) respectively.